Eksistensi Tindak Pidana Ta'zir dalam Kehidupan Masyarakat Indonesia - Ahmad Rofiq; Pujiyono Pujiyono; Barda Nawawi Arief (Journal of Judicial Review, 2021)
Ta'zir is one of the three divisions of criminal acts (jarimah) in Islamic Criminal Law. When compared with jarimah hudud and qishash diyat, jarimah ta'zir has a special character in the form of “kemaslahatan umum”. The character causes the mention of jarimah ta'zir not to be specified by the text, but rather the type and punishment handed over to ulil amri. If seen in the context of Indonesia, it is not possible to apply jarimah ta’zir in the midst of a plural society. In fact the term ta'zir is often used in referring to the penalties applied in the boarding school environment (pesantren). This research is a normative legal research. This research shows that the application of ta'zir in the pesantren environment is not just the use ofthe term alone but is the application of ta'zir as in Islamic Criminal Law. The empirical application of the concept of criminal ta'zir has actually been widely carried out in the social life of the Indonesian people. This is due to the pattern of jarimahta’zir in the form of public benefit so that in actual social life Indonesia has already implemented jarimah ta’zir